Tracking the Genomic Footprints of SARS-CoV-2 Transmission. Issue 8 (August 2020) - Lam, Tommy Tsan-Yuk
Abstract : There is considerable public and scientific interest in the origin, spread, and evolution of SARS-CoV-2. Lu et al. recently conducted genomic sequencing and analysis of SARS-CoV-2 in Guangdong, revealing its early transmission out of Hubei and shedding light on the effectiveness of controlling local transmission chains.